Susan Clegg and Her Friend Mrs. Lathrop - Warner, Anne, 1869-1913 (Salt Lake City, UT : Project Gutenberg, 2005)
"Susan Clegg and Her Friend Mrs. Lathrop" by Anne Warner is a fictional work written in the early 20th century. The story revolves around the lives of two close friends, Susan Clegg and Mrs. Lathrop, who navigate the complexities of their everyday lives, relationships, and aspirations. The opening sets a tone of humor and poignant realism, depicting Susan's often comedic struggles as she contemplates marriage while caring for her ailing father. The beginning of the novel introduces Susan, a single woman who has devoted herself to taking care of her bedridden father for many years, and her neighborly confidante, Mrs. Lathrop. Their interactions reveal Susan's longing for companionship and her humorous musings about marriage, showcasing her desire to find a husband once her father passes away. In their conversations, Susan expresses both determination and resignation about her circumstances, marking her as a relatable character facing societal expectations and personal dilemmas. The interplay between the two women establishes a strong friendship, filled with warmth, advice, and candid discussions, setting the stage for the exploration of themes related to love, duty, and the pursuit of personal happiness. (This is an automatically generated summary.)
The marrying of Susan Clegg -- Miss Clegg's adopted -- Jathrop Lathrop's cow -- Susan Clegg's cousin Marion -- The minister's vacation.
Release date is 2005-05-25
Produced by Suzanne Shell, and the Online Distributed Proofreading Team.
Keywords: Humorous stories; United States -- Social life and customs -- 20th century -- Fiction